PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN PENGELOLAAN BADAN USAHA MILIK DESA (BUMDes) DI DESA TAPENPAH KECAMATAN INSANA INDUK KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGARA TIMUR - Kiha, Emilia Khristina; Mitang, Berno Benigno (Aksara Public, 2019)
Village Owned Enterprises (BUMdes) Tapenpah Village, Insana Subdistrict, North Central Timor Regency is a newly established organization in 2017. The formation of Tapenpah village BUMdes as a form of village government efforts in improving the original opinion of the village and improving village life standards. However, without good management and support from the government and the community, the hope to make the BUMdes a locomotive of the village economy can not be realized. On the other hand, the sustainability of BUMdes will be determined by how the BUMDs can get through the first years of the establishment of the BUMdes, which is the most critical stage with the highest failure rate in the organization's life cycle. as well as the existence of standard and definite work procedure systems. Through the BUMdes management assistance program by emphasizing professionalism in management. Preparation of work planning as a work reference and supported by documented work procedures and division of tasks, authority and reporting become the strength of BUMdes in ensuring the sustainability of the organization